A Study Of The Companions Of The Prophet : Geographical Distribution And Political Alignments - Fu'ad Jabali (Insitute of Islamic Studies McGill Univercity, 1999)
ABSTRACT this dissertation deals with two aspects of the history of the Companions of the prophet : the pattern of their geographical distribution and their Political alignments-- taking as its test case the Battle of Siffin. Based on biographical dictionatics of the Companions written by selected tradisional (i.e., lbn Sa'd, lbn'Abd al-Barr, lbn al- athir, al-Dhahabi and Ibn Hajar), and on the Traditionist definition of what constitutres a Companion, an attempt will be made to identify on the one hand the Companions who setlled in lraq, Syria and Egypt, and on the other those Companions whose loyalties during the Battle of Siffin are known. Based on an analysis of the background of the Companions appearing in each of these groups and on a comparison between the two, it is argued that religious ideals played a significant role both in the Companions' movements after the death of the Prophet and in their behavior during the batlle of Siffin.